First Year Student Teachers’ Perception of Teaching Practice: A Case of Migori Teachers’ Training College - Onyango , Tom K. Omondi (African Journal of Education,Science and Technology (AJEST), 2014)
Teaching Practice (TP) for teacher trainees is central to the achievement of the Dakar and Millennium Development Goals for universalising access to primary schooling and achieving gender equity. Education Act Cap. 211 see it as an integral part of teacher education curriculum in any learning institution. This programme has three sessions of three-week period for this. The programme may include initial periods of classroom observation in, micro-teaching with peers, demonstration lessons and may provide follow up seminars and discussions building on the TP experience. TP is often the most expensive part of the initial teacher training. These include costs of travel, subsistence, supervision and assessment. The study therefore wanted to find out the First Year student teachers‟ perception on preparation and actual teaching practice. Despite this we still have serious negative issues including beating learners despite having been taught about its ban; having a poor student teacher-regular teacher relationship; negativity towards the very pupils they are supposed to have good rapport with; and poor approach to teaching. The study made use of the „technical rationality‟ model where theory and practice are taught and learned largely separately. Descriptive survey design was used and a structured questionnaire employed to collect data. This data was sieved and the relevant ones analyzed with descriptions of the results done and presented through figures and percentages. The importance of TP for professional teaching services cannot be over-emphasized contributors to which include the trainees, their teachers, the TP schools‟ regular teachers and administrators, as well as the college administrators. It is recommended that all these play their individual roles effectively to enable the pupil to benefit from the learning process during the teaching practice.